Sus sp. DNA Encoding cyt b Gene Detection Test on Meat Grinding Samples Using Conventional PCR - Adzakiyyi, Miftahul Lathif; Susilowati, Tri; Rokhim, Saiku; Rachmawati, Yuanita (UIN Sunan Gunung Djati Bandung, 2020)
Micro-entrepreneurs with basic ingredients of processed meat such as meatball who do not have a meat grinder, generally using meat grinder at the public market. The problem that occurs is that there is no clear regulation from the Government regarding the guarantee of the halal meat grinding in the Regional Company. This needs to be enhanced as a study, considering that the grinding material does not only come from Halal substances. The purpose of this study was to test pig DNA in meat grinding samples at PD Pasar Surya Surabaya City by using the conventional Polymerase Chain Reaction (PCR) method. DNA was isolated from 11 PD Pasar Surya meat grinding samples, then spectrophotometry was performed. Spectrophotometry results showed that all samples have high DNA concentrations. The primer used is the cyt b pig gene encoder. Predenaturation is performed at a temperature of 95°C-5 minutes, denaturation of 95°C-45 seconds, annealing 60°C-30 seconds, extension 72°C-40 seconds, and post extension 72°C-5 minutes. The results of PCR analysis were determined by the emergence of DNA bands of ± 149 bp as markers of pig DNA. The results showed negative on sample or no pig contamination in 11 samples tested. While the pig sample as positive control showed a band of ± 149 bp. These results prove that at 11 points of the location of meat grinding there is no contamination of pig DNA.